Analytical study on the current state of development of the companion industry - Yuan, Yu; Chen, Xingchi; Zhang , Qirui; Xu, Ruihan; Jiang, Jing (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Chaperone Service are designed to save time and effort by assisting patients with hospital visits, including registration, queuing, and billing. This article summarises the theoretical foundations of the professional escort field, developments, the definition of the concept of the escort service industry, the concept of the escort, the distinction between the escort and the traditional care worker and the "ticket scalper" robbing the number on behalf of the patient, as well as the demand for talents and competencies of the escort and the traditional care worker and the "ticket scalper" robbing the number comparison. The article also analyses in detail the healthcare resource models in the escort service industry, including escort service platforms, hospitals' own escort channels, and cooperation between hospitals and escort agencies. These analyses help to understand the current situation of the escort service industry, the definition of the concept, the comparison of the talent demand, and the different service models, so as to better develop this industry.